2021
DOI: 10.3390/biomedicines9070776
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Safe and Effective Coaguligands for Vascular Targeting and Precision Thrombosis of Solid Tumors and Vascular Malformations

Abstract: In cardiovascular and cerebrovascular biology, control of thrombosis and the coagulation cascade in ischemic stroke, myocardial infarction, and other coagulopathies is the focus of significant research around the world. Ischemic stroke remains one of the largest causes of death and disability in developed countries. Preventing thrombosis and protecting vessel patency is the primary goal. However, utilization of the body’s natural coagulation cascades as an approach for targeted destruction of abnormal, disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 125 publications
(183 reference statements)
0
4
0
Order By: Relevance
“…PS is an abundant phospholipid that flips from the inner surface of the plasma membrane to the outer surface in response to a variety of biological stimuli, including radiation, and is most often observed in apoptotic cells [ 28 , 29 , 30 ]. The higher efficacy may reflect greater levels of PS exposure at the surface relative to PDCE2 and CRYAB or, alternatively, could reflect the relative affinity of each ligand for their respective targets [ 1 ]. A recent in vivo investigation of PS targeting in a rat AVM model revealed that both irradiated and non-irradiated vasculature could be thrombosed with a high affinity PS-targeting VTA [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PS is an abundant phospholipid that flips from the inner surface of the plasma membrane to the outer surface in response to a variety of biological stimuli, including radiation, and is most often observed in apoptotic cells [ 28 , 29 , 30 ]. The higher efficacy may reflect greater levels of PS exposure at the surface relative to PDCE2 and CRYAB or, alternatively, could reflect the relative affinity of each ligand for their respective targets [ 1 ]. A recent in vivo investigation of PS targeting in a rat AVM model revealed that both irradiated and non-irradiated vasculature could be thrombosed with a high affinity PS-targeting VTA [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vascular targeting with precision thrombosis is an approach aimed at occlusion and destruction of pathological vasculature in tumors and brain arteriovenous malformations (AVMs) [ 1 , 2 , 3 ]. This approach requires the identification of discriminatory biomarkers at the luminal surface of the pathological endothelium for use as molecular targets for the focused delivery of thrombogenic agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] Suboptimal embolization of large tumor vessels is one of the main challenges of current treatment strategies. [8,20,21] The intensity of the induced coagulation effect in the tumor large vessels directly determines the final embolic effect, and the development of more intense and sensitive coagulation initiation modalities is an urgent requirement to further promote the development of tumor thrombosis infarction therapy. Moreover, the coagulation-cascade effect in the tumor vasculature forms thrombus after initiation, while the fibrinolytic system is also activated.…”
Section: Introductionmentioning
confidence: 99%